2003
DOI: 10.1063/1.1568546
|View full text |Cite
|
Sign up to set email alerts
|

Oriented single-crystal diamond cones and their arrays

Abstract: One of the major problems in material science has been the difficulty in modification of the most endurable material, diamond, due to its extreme hardness and chemical inertness. Here, we report the development of a conical structure of diamond by performing bias-assisted reactive ion etching in hydrogen plasma. The diamond cones produced by this method are uniformly distributed over large areas on silicon substrates. Each cone was identified to be a single crystal with an apical angle as small as 28° and a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…5 Such an explanation is plausible in this experiment, because the aforementioned diamond cone formation process was performed in a H-containing ambience. H desorption from sp 3 emitting sites can occur at temperature of ϳ500 K, 18 and loss of H atoms from local emitting sp 3 sites can increase the surface work function.…”
Section: Z Cuimentioning
confidence: 98%
See 1 more Smart Citation
“…5 Such an explanation is plausible in this experiment, because the aforementioned diamond cone formation process was performed in a H-containing ambience. H desorption from sp 3 emitting sites can occur at temperature of ϳ500 K, 18 and loss of H atoms from local emitting sp 3 sites can increase the surface work function.…”
Section: Z Cuimentioning
confidence: 98%
“…Zhang et al reported the FEE properties of diamond cone arrays formed by bias-assisted reactive etching process. 5,6 However, the FEE properties of individual diamond cone, which can present the intrinsic FEE properties of diamond cone due to the exclusion of field shield effect, have not been studied so far. Recently, a maskless technique using ion sputtering has been developed for the formation of sharp silicon cone arrays on porous silicon.…”
Section: Z Cuimentioning
confidence: 99%
“…Recently, the fabrication of characteristic surfaces for diamond and diamond-like carbon (DLC) has drawn considerable attention due to the excellent physical and chemical properties of these materials [1][2][3][4][5][6][7][8]. With the negative electron affinity, for instance, they have been expected as the most promising field emission materials with a low threshold field to be applied in electron sources, flat panel displays, and a new generation of microwave tubes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Zhang et al modified the surface structures of the as-formed diamond films during microwave plasma chemical vapor deposition, oriented cone arrays of diamonds were developed by employing bias-assisted hydrogen ion etching [1,2]. Zhu et al reported the formation of cone, ripple, and pyramid structures for amorphous diamond-like carbon with an ion beam assisted deposition, and film surfaces could be tuned by controlling the deposition parameters to drive the competition between ion sputtering and carbon deposition [3].…”
Section: Introductionmentioning
confidence: 99%
“…The removal of the material starts from the grain boundaries, and the process proceeds by sharpening the isolated nanograins to obtain the final conical features as a consequence of an etching rate that is faster across the height of the gradually protruding diamond structures. [95][96][97] A programmed treatment consisting of nitrogen plasma immersion ion implantation has been carried out on crystalline diamond nanotips (∼1 µm in height, ∼200 nm bottom diameter) produced by MW-enhanced CVD. 78 After the nitrogen treatment a turn-on field of 3 V μm −1 and a current density up to 4 mA cm −2 at the applied field of 9 V μm −1 were measured.…”
Section: D Structuresmentioning
confidence: 99%